Stanowisko Jana Długosza wobec cudzoziemskich władców na tronie polskim - Obara-Pawłowska, Anna (Średniowiecze Polskie i Powszechne, 2019)
The aim of the following article is to present the attitudes of Jan Długosz towards the issue of crowning the representatives of foreign dynasties as kings of Poland. Thus, the article focus‑ es on Długosz’s opinions regarding the following rulers of Poland: Wenceslaus II of Bohemia, Louis I of Hungary and Władysław II Jagiełło, who all came to Poland from the neighboring countries and who represented dynasties other than the Piast dynasty. To this end, the article presents Długosz’s opinions regarding the ascensions of foreign monarchs to the throne in the Kingdom of Poland, as well as discusses both the benefits and the disadvantages of having a foreign ruler on the throne, included in his Annales. In the last section of the article, refer‑ ring to the descriptions of the monarchs’ reigns found in Długosz’s opus magnum, attempts to ascertain the influence of their foreign (ethnically, religiously or culturally) ancestry on the subject matter of Długosz’s comments.